Development strategy for COGEN : an action research approach - Lacrosse, Ludovic; Johri, Lalit M.; Swierczek, F.W.; Tocquer, Gerard A.; PTS European (Pathum Thani, Thailand : Asian Institute of Technology, 2001)
Building on eight years experience and on the strengths of the team that had operated the biomass energy-related EC-ASEAN COGEN Programme, a new COGEN Center was created at AIT in February 2000. Most of its first year of activities was spent offering customized studies to Thai wood and agro- industries, aiming at helping them optimize the use of their residues for energy. A SWOT analysis revealed that COGEN had developed strong competitive advantages through the high competence of its team that can offer high value- added customized services at a very competitive price. A business development strategy was prepared. It integrates COGEN's relation with AIT, with its clients, partners and competitors, as well as COGEN's marketing and internal organization. Particular attention is paid to the management of the relationship of COGEN with its customers. The Customer Relationship Management Value Chain Model is used. COGEN team productivity was analysed. It reveals that COGEN shows most weaknesses of a young structure, i.e. a lack of experience, a shortage of staff, and limited financial resources. These problems are being tackled by the organization of regular internal COGEN seminars. An action plan is presented. If well implemented, it will help COGEN consolidate and reach its long-term sustainability before the end of 2001.
A research study submitted in partial fulfillment of the requirements for the degree of Master in Business Administration (Executive MBA Program)
Research Studies Project Report (M.B.A.) - Asian Institute of Technology, 2001
Keywords: Strategic planning; Business -- Research -- Methodology